Primary rectal ectopic pregnancy: a rare case report and literature review - Zhang, Qun; Yang, WenJie; Wang, BoWei (Frontiers in Medicine, 2025)
BackgroundRectal ectopic pregnancy is classified into primary and secondary types, with primary rectal ectopic pregnancy being one of the rarest forms of extrauterine gestation. Currently, there are no standardized guidelines for its diagnosis and treatment.Case presentationWe present a case of primary rectal ectopic pregnancy in a 37-year-old woman with acute abdominal pain and massive intra-abdominal hemorrhage. Under the premise of gynecological ultrasound suggesting conventional tubal or ovarian ectopic pregnancy, we employed diagnostic single-port laparoscopy to exclude typical adnexal pregnancies. Through comprehensive exploration of both the upper and lower abdominal cavities, we ultimately confirmed the diagnosis of primary rectal ectopic pregnancy. And through coordinated efforts with gastrointestinal surgeons, we performed precise resection of the ectopic gestational tissue while preserving rectal integrity, with prompt control of intra-abdominal hemorrhage. This emergency intervention achieved dual success: lifesaving management coupled with minimally invasive advantages, Enhanced recovery after surgery and resulting in a nearly invisible umbilical incision with optimal cosmetic outcomes.ConclusionPatients with rectal ectopic pregnancy often present with nonspecific early symptoms, leading to frequent misdiagnosis or delayed diagnosis. Definitive diagnosis is typically established only after the onset of severe complications. Through a multidisciplinary approach to this rare case and a systematic review of the literature, we have derived the following important clinical insights: 1. Early diagnosis strategy: early identification of REP requires a multimodal approach, including dynamic monitoring of serum β-hCG levels, pelvic ultrasound, and multimodal imaging assessment with CT/MRI. Diagnostic laparoscopy should be performed when necessary to confirm the location and extent of the lesion. 2. Broadening differential diagnosis considerations: in all women of childbearing age who are considered to be pregnant, especially when intrauterine, tubal, or ovarian pregnancy is not detected by ultrasound, REP should be included in the differential diagnosis. 3. Value of Minimally Invasive Surgery: Single-port laparoscopic surgery has demonstrated comprehensive advantages in such emergency surgeries, including minimal invasiveness, rapid recovery, and cosmetic benefits. However, this technique requires the surgeon to possess advanced skills, and the patient must meet the indications for single-port laparoscopic surgery. This article also provides important reference evidence for the development of standardized diagnostic and treatment protocols for rectal ectopic pregnancy.